Social policies and decentralization - Francke Ballve, Pedro (2004)
With little progress in fundamental aspects of social policy, the Government has launched the decentralization process. In this way, it seems that decentralization will be the main reform of the social sectors during the present Government. The decentralization of the social sectors and programs can be a process of great importance to: a) support the decentralization to become effective, developing a better link between representatives and represented that strengthens democracy and governability; b) improve the effectiveness and efficiency of these basic services and anti-poverty programs, making them more adapted to local and regional realities, increasing social participation in their design and management, and making public leaders and managers more interested in the quality of its management.